Study and evaluation of white clover samples as a source material for selection in the conditions of Precarpathian - О. R. PEREHRYM (Передгірне та гірське землеробство і тваринництво, 2022)
One of the most common perennial legume grasses of Precarpathian, a valuable component of grass mixtures in improving natural hayfields and creating cultivated pastures is white clover (Trifolium repens L.). It tolerates trampling and grazing by animals, is more winter hardy, and by protein content do not concede to red clover and hybrid clover. Due to the ability of nitrogen fixation thanks to  presence of nodule bacteria on its roots, the agrophysical, agrochemical and biological properties of the soil are improved. An important role in the formation of the productivity of white clover belongs to the variety, which is achieved by conducting selection work, the first and main stage of which is the study and evaluation of initial material.